Inhibition of histone deacetylases 3 attenuates imiquimod-induced psoriatic dermatitis via targeting cGAS-STING signaling in keratinocytes - Chong Zeng; Xiujuan Wen; Zibo Wei; Xinhuai Dong (Journal of Translational Medicine)
Abstract Background Psoriasis is a common chronic inflammatory skin disease characterized by epidermal keratinocyte hyperproliferation and persistent immune activation. Histone deacetylase 3 (HDAC3), a member of the class I HDAC family, plays critical roles in regulating immunity and inflammation. However, its precise expression profile and functional contribution to psoriasis pathogenesis remain poorly defined. Methods We first performed bioinformatics analysis of HDAC3 expression using the Gene Expression Omnibus (GEO) database. Subsequently, we employed a combination of cellular and molecular techniques, including hematoxylin and eosin (H&E) staining, immunohistochemistry, flow cytometry, quantitative real-time PCR (qRT-PCR), western blotting, and transmission electron microscopy (TEM), to analyze the role of HDAC3 in IMQ-induced psoriasis-like inflammation in mice and in vitro psoriasis models. Results HDAC3 expression was significantly upregulated in psoriasis lesions of patients and in both in vitro and in vivo models of psoriasis. Pharmacological inhibition of HDAC3 using the specific inhibitor RGFP966 alleviated IMQ-induced skin inflammation in mice and suppressed psoriasis-like phenotypes in vitro. Mechanistically, HDAC3 upregulation in an inflammatory microenvironment promoted oxidative stress, disrupted mitochondrial structural integrity, and triggered mitochondrial DNA leakage into the cytosol, thereby activating the cGAS-STING pathway in keratinocytes. Conclusion Our findings establish HDAC3 as a pivotal mediator of psoriasis pathogenesis through the cGAS-STING pathway via mitochondrial dysfunction. The role of HDAC3 in exacerbating epidermal hyperproliferation and inflammation highlights its potential as a therapeutic target. Targeting HDAC3 in keratinocytes may offer a novel strategy for preventing and treating psoriasis by modulating epigenetic regulation, mitochondrial homeostasis, and innate immune responses.